2023
DOI: 10.1038/s41591-023-02520-3
|View full text |Cite
|
Sign up to set email alerts
|

Subretinal timrepigene emparvovec in adult men with choroideremia: a randomized phase 3 trial

Robert E. MacLaren,
M. Dominik Fischer,
James A. Gow
et al.

Abstract: Choroideremia is a rare, X-linked retinal degeneration resulting in progressive vision loss. A randomized, masked, phase 3 clinical trial evaluated the safety and efficacy over 12 months of follow-up in adult males with choroideremia randomized to receive a high-dose (1.0 × 1011 vector genomes (vg); n = 69) or low-dose (1.0 × 1010 vg; n = 34) subretinal injection of the AAV2-vector-based gene therapy timrepigene emparvovec versus non-treated control (n = 66). Most treatment-emergent adverse events were mild or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 35 publications
(47 reference statements)
0
6
0
Order By: Relevance
“…In contrast, the number of patients gaining two lines of vision was statistically significant compared to the control group. Unfortunately, this did not reach the primary endpoint, and hence, there was no regulatory approval [ 91 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the number of patients gaining two lines of vision was statistically significant compared to the control group. Unfortunately, this did not reach the primary endpoint, and hence, there was no regulatory approval [ 91 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results of the STAR Phase III clinical trial have recently been reported. 42 In the primary end-point analysis, 3 of 65 participants (5%) in the high-dose group, 1 of 34 (3%) participants in the low-dose group and 0 of 62 (0%) participants in the control group had ≥ 15-letter ETDRS improvement from baseline BCVA at 12 months (high dose, p = 0.245 vs. control; low dose, p = 0.354 vs. control). As the primary end point was not met, key secondary end points were not tested for significance.…”
Section: Future Investigationsmentioning
confidence: 91%
“…AO-guided microperimetry studies have shown that retinal sensitivity is preserved within areas with contiguous cone mosaics, while dense scotomas are evident in atrophic areas [84]. Fundus-guided microperimetry has been performed in clinical trials evaluating treatments for CHM; however, given the advanced stage of the disease in these participants, the microperimetry data were generally found to be inconsistent [85][86][87]. Thus, to summarize, the main outcome measures to assess retinal structure adopted in clinical trials testing gene therapy in choroideremia are EZ preservation area and RPE preservation area evaluated by OCT and FAF, respectively [86][87][88][89].…”
Section: Choroideremia (Chm)mentioning
confidence: 99%